2019
DOI: 10.1007/s00421-019-04238-y
|View full text |Cite
|
Sign up to set email alerts
|

One week of magnesium supplementation lowers IL-6, muscle soreness and increases post-exercise blood glucose in response to downhill running

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRaP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…, 44, 46, 50, 59-62, 65-67, 70, 72-75, 77, 80, 81, 84, 85, 87-90, 92, 121, 134-183] and DOMS[8,15,38,58,60,66,71,75,84,89,135,151,156,159,171,178,179,182,[184][185][186][187][188] peak from 24 to 48 h post-DR. Immediately post DR, a greater reduction in isometric MVC force/torque is observed in untrained (mean: − 23.5%; 95% CI: [− 26.9% to − 17.2%] compared to trained populations (− 16.4%; 95% CI: [ − 19.5% to -12.3%]).…”
mentioning
confidence: 99%
“…, 44, 46, 50, 59-62, 65-67, 70, 72-75, 77, 80, 81, 84, 85, 87-90, 92, 121, 134-183] and DOMS[8,15,38,58,60,66,71,75,84,89,135,151,156,159,171,178,179,182,[184][185][186][187][188] peak from 24 to 48 h post-DR. Immediately post DR, a greater reduction in isometric MVC force/torque is observed in untrained (mean: − 23.5%; 95% CI: [− 26.9% to − 17.2%] compared to trained populations (− 16.4%; 95% CI: [ − 19.5% to -12.3%]).…”
mentioning
confidence: 99%
“…muscle cramps) can have a meaningful outcome in their performance. While magnesium can help with nocturnal leg cramps, data on whether endurance athletes can benefit from magnesium supplementation using a hydration beverage are lacking despite some evidence that magnesium supplementation in athletes can reduce inflammation and help with recovery 10,11 . One of the challenges is to deliver an optimal amount of magnesium that can be quickly absorbed via the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no marked influence on plasma pro-inflammatory cytokines TNF-α and IL-1β following DH running was observed. Numerous studies have reported that eccentric exercise promotes inflammatory reactions by mediating leukocyte function and inflammatory cytokine secretion [ 46 , 53 , 54 , 55 , 56 , 57 ]. Exceedingly high or chronic expression of pro-inflammatory cytokines may contribute to the ROS generation capability of leukocytes or the impairment of muscle regeneration and repair, resulting in longer processes for returning the pre-exercise performance [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in this manuscript, IL-6 is the most frequently changed inflammatory cytokine following eccentric exercise with low to moderate intensity and duration [ 53 , 56 ]. A review article suggested that there is no significant association between local and systemic cytokine responses to exercise besides IL-6 [ 62 ].…”
Section: Discussionmentioning
confidence: 99%